2015
DOI: 10.1371/journal.pone.0127906
|View full text |Cite
|
Sign up to set email alerts
|

Macular Microcysts in Mitochondrial Optic Neuropathies: Prevalence and Retinal Layer Thickness Measurements

Abstract: PurposeTo investigate the thickness of the retinal layers and to assess the prevalence of macular microcysts (MM) in the inner nuclear layer (INL) of patients with mitochondrial optic neuropathies (MON).MethodsAll patients with molecularly confirmed MON, i.e. Leber’s Hereditary Optic Neuropathy (LHON) and Dominant Optic Atrophy (DOA), referred between 2010 and 2012 were enrolled. Eight patients with MM were compared with two control groups: MON patients without MM matched by age, peripapillary retinal nerve fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
4
16
0
1
Order By: Relevance
“…In such studies, retinal microcysts were more prominent in the parafoveal area, corresponding to the area with the largest concentration of both Müller and ganglion cells ( 61 ). Researchers ( 20 , 62 ) have suggested that vitreous traction could be associated with the occurrence of INL microcysts, but we find it an unlikely pathogenic factor, since in a previous study, the microcysts were restricted to the nasal hemiretina of eyes with temporal hemianopia and BA of the optic nerve ( 22 ), making it unlikely that the vitreous would draw only the hemiretina with severe GCL loss. In view of the importance of Müller cells for the maintenance of the retinal framework, we believe that RGC atrophy may have a tractional effect on Müller cells, resulting in increased thickness in areas with RGC damage.…”
Section: Discussionmentioning
confidence: 60%
“…In such studies, retinal microcysts were more prominent in the parafoveal area, corresponding to the area with the largest concentration of both Müller and ganglion cells ( 61 ). Researchers ( 20 , 62 ) have suggested that vitreous traction could be associated with the occurrence of INL microcysts, but we find it an unlikely pathogenic factor, since in a previous study, the microcysts were restricted to the nasal hemiretina of eyes with temporal hemianopia and BA of the optic nerve ( 22 ), making it unlikely that the vitreous would draw only the hemiretina with severe GCL loss. In view of the importance of Müller cells for the maintenance of the retinal framework, we believe that RGC atrophy may have a tractional effect on Müller cells, resulting in increased thickness in areas with RGC damage.…”
Section: Discussionmentioning
confidence: 60%
“…As for LHON, macular GC-IPL thickness measurements could prove a more useful structural biomarker that correlates better with visual acuity loss compared with peripapillary RNFL values [18]. Another observation made possible by high-resolution OCT imaging is the documentation of microcystic macular changes in the inner nuclear layer of patients with LHON and DOA [17, 29]. These retinal abnormalities are not associated with leakage on fluorescein angiography and they have been attributed to focal retinal schisis induced by vitreous traction on the background of severe RNFL atrophy.…”
Section: Neurodegeneration: In Vivo Imagingmentioning
confidence: 99%
“…[14][15][16] Several mechanisms have been proposed to explain the development of INL pseudo-cysts, including retinal inflammation, breakdown of the blood-retinal barrier, trans-synaptic degeneration of neurons within the INL and/or traction by the vitreous. 14,[16][17][18][19][20] However, none of these have been established, nor have any been able to account for the complete spectrum of findings observed in these cases (discussed below). 13 ).…”
Section: ''Microcystic Macular Edema'' (Inner Nuclear Layer Pseudo-cymentioning
confidence: 99%
“…As mentioned above, several potential mechanisms have been proposed to explain the development of microcystic macular edema. 14,[16][17][18][19][20] However, none are completely satisfactory in the context of the following considerations. First, cystoid lacunae develop within the INL only where the more proximal retinal layers (RNFL, GCL, and IPL) are thickest in healthy retina, but have undergone rapid degeneration due to loss of retinal ganglion cells and their axons.…”
Section: Proposed Refinement Of a Mechanical Explanation For Inl Pseumentioning
confidence: 99%